Gentrificação urbana e o processo de desenvolvimento do Bairro Cidade Nova, Ananindeua - Pa - SILVA, Luana Patrícia Viana da (2024)
The work discusses about gentrification in the New City set, in Ananindeua – PA, Secondarily it was possible to collect together the main theme the conceptualization of Gentrification and the process of capitalism within this context. The research carried Out sought to understand the gentrification on the cities of the Amazon as the Metropolitan Region of Belém, consecutively with the process of gentrification in the City of Ananindeua in particular, the neighborhood of the New City. In view of this Concern, the following objective was established: to understand the process and Concept of gentrification as a current theme, to contextualize and present it. There was A concentration of research in the city of Ananindeua and its Cidade Nova Neighborhood, describing the parameters obtained by this concept, presenting the Most iconic experiences of the gentrification of this region and its relationship with the Concepts and processes. In the discussion, the analysis is positioned from the. Theoretical and methodological perspective of the social production of space and Enumerates the categories, concepts and notions considered important for the Understanding of the issue. Therefore, a bibliographic survey was carried out to find The possible answers raised about the hypotheses. The emphasis is placed on the Urban form as a starting point for the discussion of the metropolitan restructuring of Belém, Ananindeua and the neighborhood of the New City, on na Amazonian context, And on the dialectic of the relationship between structure and action as a possible way To carry out this type of analysis.